African-American History is American History: Expanding the National Narrative in the Smithsonian Institution. - LaCroix, Allison. (2017)
Abstract: Deeply entrenched notions of American exceptionalism have long dominated the national narrative within the United States. This narrative, often presented by and reflective of white American men, has historically controlled many of the Smithsonian Institution's museums, confining exhibit content to patriotic and celebratory parameters. With the rise of the Civil Rights Movement in the 1960s, however, gaps in this predominant American narrative gained wider consideration, and the often-obscured histories of various cultural groups, including African Americans, began to gain prominence in the field of public history. Museums have played a significant role in expanding the national narrative to be more inclusive of groups of different racial and cultural backgrounds. As a federally-funded public institution located in the nation's capital, however, many of the Smithsonian Institution's museums, including the National Museum of American History (NMAH), the National Museum of American Art (NMAA), the National Air and Space Museum (NASM), and the National Museum of the American Indian (NMAI), have struggled for decades to define their role as educational institutions in contributing to a broader understanding of a culturally diverse America. The development of the National Museum of African American History and Culture (NMAAHC), under the leadership of Lonnie G. Bunch III, serves as a turning point for the Smithsonian, as it reflects the knowledge gleaned from past controversies faced by other Smithsonian museums. With an emphasis on curatorial authority and reliance on historical scholarship, the NMAAHC will help expand the American national narrative to be more inclusive, ultimately making clear that African-American history is American history.; Thesis (M.A.)--Tufts University, 2015.; Submitted to the Dept. of History.; Advisor: Kendra Field.; Committee: Cara Iacobucci, and Peniel Joseph.; Keywords: Museum studies, African American studies, and History.